Rodzina w dramacie kobiecym: po przełomie 1989 roku, a w latach 30. XX wieku - Kot, Joanna (Postscriptum Polonistyczne, 2020)
The article compares two groups of ‘women’s’ drama, one written during the interwar period, the other after the changes of 1989. On the one hand, the analysis presents the image of family emerging in these two groups of plays from a feminist perspective. On the other hand, the article raises the question of their form, since it so strongly influences the reception of these works. A comparison of plays written after 1989 with those created during the interwar period demonstrates the historical continuity of family issues that have not been solved till present day. Concurrently, in terms of form, it shows that combining traditional elements with innovative ones leads to the greatest dramatic effectiveness.